Earnings management, its motives and trends in the context of the development of accounting theories - Cibutavičiūtė, Viltė; Bachtijeva, Diana (Buhalterinės apskaitos teorija ir praktika, 2024)
The paper examines the concept of earnings management, including its characteristics and motives for use as presented in scientific literature. A matrix of firm and managerial motive clusters is presented in the light of the opportunistic behaviour hypotheses of positive accounting theory. The paper analyses the various types of earnings management practices and discusses profit-reducing and profit-enhancing accounting methods. It also explores the trends in the use of different types of earnings management and the reasons behind them, which can be divided into three phases. The normative period of accounting theories was characterised by the widespread use of accrual-based earnings management. During the positive period of accounting theory development, there was an increase in the practice of real earnings management. The evolution of accounting theories, improvements in auditing practices, and changes in accounting policies led to shift away from accrual-based to real earnings management.
Keywords: earnings management; positive accountings theory; accrual-based earnings management; real earnings management